Management model for social and environmental impact in logistics through blockchain technologies - Peter Verhoeven (Universitätsverlag der TU Berlin, 2022)
In the context of the advancing digitalization of logistics processes, blockchain technologies are gaining in importance. Within the scope of sustainable logistics networks, they contribute to cross-stakeholder transparency and support the tracking and verification of products and processes to improve social and environmental parameters. The goal of this work is to develop a holistic management model to help users understand blockchain technologies in the context of their logistics network and to assess the mindful adoption of these technologies to specific problems. In addition, the model should enable the conclusion of expected impacts on participating actors within the logistics network with regard to social and environmental sustainability and, in a further step, provide a holistic approach to the implementation of blockchain technologies. Methodologically, a systematic literature analysis, two workshops and a case study exploration will be conducted for this purpose. Within the systematic literature analysis, 285 articles are evaluated and 53 relevant articles are synthesized. Based on the Nominal Group Technique, a first workshop with 30 experts from manufacturing companies, logistics service providers, technology companies and universities will be conducted and supplemented by a subsequent survey. In a second workshop, three use cases of blockchain technologies are analyzed with 24 experts in open and moderated group discussions. Finally, three exemplary case studies and eight expert interviews are conducted and systematically evaluated with respect to cross-case findings. The result of this thesis is a four-phase management model that guides users through the process of evaluating and implementing blockchain technologies in the context of sustainable logistics. While the first phase assesses requirements of the logistics network for general applicability of blockchain technologies, the second phase includes a model for the mindful adoption of blockchain technologies. Based on this, phase three provides a sustainability impact model to explain social and environmental impacts of individual actors involved in the logistics network. The fourth phase ultimately represents the implementation of blockchain technologies in logistics and is based on five management areas in which specific design recommendations, methods and tools are provided to enable a successful implementation. Finally, the thesis provides an outlook on a future vision and shows which changes in logistics networks can be expected due to blockchain technologies. – – Im Rahmen der voranschreitenden Digitalisierung von Logistikprozessen gewinnen Blockchain-Technologien zunehmend an Bedeutung. Sie leisten im Kontext nachhaltiger Logistiknetzwerke einen Beitrag zur akteursübergreifenden Transparenz und unterstützen die Nachverfolgung und Verifizierung von Produkten und Prozessen zur Verbesserung sozialer und ökologischer Parameter. Ziel dieser Arbeit ist es, ein ganzheitliches Management Modell zu entwickeln, das Anwender dabei unterstützt, Blockchain-Technologien im Kontext ihres Logistiknetzwerks zu verstehen und die achtsame Anwendbarkeit dieser Technologien für spezifische Problemstellungen zu prüfen. Zudem soll das Modell eine Ableitung der zu erwartenden Effekte auf beteiligte Akteure innerhalb des Logistiknetzwerkes hinsichtlich der sozialen und ökologischen Nachhaltigkeit ermöglichen und in einem weiteren Schritt einen ganzheitlichen Ansatz zur Implementierung von Blockchain-Technologien bereitstellen. Methodisch werden dafür eine systematische Literaturanalyse, zwei Workshops sowie eine Fallstudienuntersuchung durchgeführt. Im Rahmen der systematischen Literaturanalyse werden 285 Artikel ausgewertet und 53 relevante Artikel synthetisiert. Basierend auf der Nominal Group Technique wird ein erster Workshop mit 30 Experten von Fertigungsunternehmen, Logistikdienstleistern, Technologieunternehmen und Hochschulen durchgeführt und durch eine anschließende Befragung ergänzt. Im Rahmen eines zweiten Workshops werden drei Anwendungsfälle von Blockchain-Technologien mit 24 Experten in offenen und moderierten Gruppendiskussionen analysiert. Abschließend werden drei exemplarische Fallstudien sowie acht Experteninterviews durchgeführt und systematisch hinsichtlich fall-übergreifender Erkenntnisse ausgewertet. Das Ergebnis dieser Arbeit ist ein vierphasiges Management Modell, dass den Anwender durch den Prozess der Bewertung und Implementierung von Blockchain-Technologien im Kontext nachhaltiger Logistik führt. Während in der ersten Phase Anforderungen des Logistiknetzwerks auf generelle Eignung für Blockchain-Technologien geprüft werden, umfasst die zweite Phase ein Modell für die achtsame Adoption. Darauf aufbauend wird in Phase drei ein Modell zur Erklärung sozialer und ökologischer Effekte einzelner beteiligter Akteure des Logistiknetzwerks bereitgestellt. Die vierte Phase repräsentiert letztlich die Implementierung von Blockchain-Technologien in der Logistik und basiert auf fünf Managementbereichen, in denen gezielt Handlungsempfehlungen, Methoden und Werkzeuge bereitgestellt werden, um eine erfolgreiche Umsetzung zu ermöglichen. Abschließend gibt die Arbeit einen Ausblick auf eine zukünftige Vision und zeigt auf, welche Veränderungen in Logistiknetzwerken durch Blockchain-Technologien zu erwarten sind.
Keywords: 650; logistics; blockchain; sustainability; DLT; transparency; Logistik; Blockchain; Nachhaltigkeit; DLT; Transparenz